Cascade Michael–Intramolecular Transesterification–Elimination Reaction of 3, 4‐Dihydro‐3‐nitrochromen‐2‐ones and β, γ‐Unsaturated α‐Oxo Esters: An Efficient Access to 2‐Pyrone Derivatives. Issue 15 (7th April 2014) - Zhang, Li; Wang, Youming; Song, Haibin; Zhou, Zhenghong; Tang, Chuchi
Abstract: Multisubstituted 2‐oxopyran‐6‐carboxylic acid derivatives were synthesized under mild reaction conditions through a base‐promoted reaction between 3, 4‐dihydro‐3‐nitrochromen‐2‐ones and β, γ‐unsaturated α‐oxo esters to give products in excellent yields. The reaction is believed to proceed through a cascade Michael–intramolecular transesterification–elimination process. Abstract : A new base‐promoted cascade Michael–intramolecular transesterification‐elimination reaction of 3, 4‐dihydro‐3‐nitrochromen‐2‐ones and β, γ‐unsaturated α‐oxo esters has been developed. This process provides an efficient approach to the synthesis of multifunctionalized 2‐pyrone derivatives.